Genome-Wide Knockout Screen Identifies EGLN3 Involving in Ammonia Neurotoxicity - Li, Jiequn; Chen, Chunli; Li, Chenchen; Hu, Zhiping; Tan, Jieqiong; Zeng, Liuwang (Frontiers in Cell and Developmental Biology, 2022)
Hepatic encephalopathy (HE) is a brain dysfunction associated with poor quality of life, increased morbidity and mortality. The pathogenesis of HE is still not fully clarified and effective therapeutic strategies are imperative. Among multiple factors that contribute to the pathophysiological process of HE, ammonia neurotoxicity is thought to be central in the pathogenesis of HE. Therefore, in this study, we subjected SH-SY5Y cells to ammonia insult and performed a pooled genome-wide CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 (CRISPR-associated protein 9) knockout screen to unveil the underlying molecular mechanisms of ammonia neurotoxicity and discover new potential therapeutic targets for HE. We found that EGLN3(egl-9 family hypoxia-inducible factor 3),UCP3,GTPBP5,OR4D11 and SDR9C7 with 6 unique sgRNAs may contribute to protection against ammonia injury, while EGLN3 may be most related to ammonia resistance. We knocked down EGLN3 by transfecting neurons with specific shRNA lentivirus and confirmed that EGLN3 knockdown decreased ammonia‐induced caspase-3 activation and apoptosis. We also demonstrated that EGLN3 knockdown ameliorated ammonia induced decreased expression of Bcl-2, increased expression of Bax and inhibited release of cytochrome c into the cytosol in neurons, suggesting that EGLN3 inhibition protected against ammonia induced apoptosis through mitochondrial dependent apoptosis pathway. Future therapeutic strategies regulating EGLN3 may be applied to the management of HE.